2009
DOI: 10.1016/j.actao.2009.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Evidence against the use of fecal pellet size for age determination in European wild rabbits

Abstract: a b s t r a c t Techniques for estimating the age of wild animals are crucial to many aspects of the study of population biology. Accurate estimates of the proportion of different age classes in wild rabbit populations would be very useful, and the possibility that it could be obtained from the pellet size holds great appeal. However, this suggestion has created controversy in the literature as this technique has not been validated. This study involved assessment of whether threshold fecal pellet diameters cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…There is often controversy with the development of ecological indices and their effectiveness in reality. Therefore, it is essential to carry out case‐specific verification and validation for each species (Delibes‐Mateos et al 2009, Rouco et al 2009). We therefore performed a cross‐validation using a subsample of our data (Conroy & Carroll 2009).…”
Section: Methodsmentioning
confidence: 99%
“…There is often controversy with the development of ecological indices and their effectiveness in reality. Therefore, it is essential to carry out case‐specific verification and validation for each species (Delibes‐Mateos et al 2009, Rouco et al 2009). We therefore performed a cross‐validation using a subsample of our data (Conroy & Carroll 2009).…”
Section: Methodsmentioning
confidence: 99%
“…A key part of this management is population monitoring. The use of feces is a common monitoring approach for the study of many terrestrial mammals (Chame 2003;Rouco et al 2009;Lonsinger et al 2015), including ungulates (Cromsigt et al 2009). Fecal pellets can be collected non-invasively in large numbers and with relative ease.…”
Section: Introductionmentioning
confidence: 99%
“…We measure the maximum diameter of pellets (nondried) using a digital sliding calibre (accuracy of 0.01 mm) because it is considered to be the decisive measurement limiting the chance that a pellet will pass through a grid with a given mesh size in order to differentiate between juvenile and adult rabbits (cf. Rueda et al 2008;Rouco et al 2009). Data were collected from May to early December in the years 2007, 2008 and 2009.…”
mentioning
confidence: 97%
“…Accordingly, it has been suggested that pellet size or pellet size cut values could be used to assign individuals to an age-class for some mammal species (Southgate 2005;Rueda et al 2008;Ball 2010). However, the usefulness of this field method in mammals is still controversial, and in particular for the European rabbit (Oryctolagus cuniculus) its practicability has been put into question Rouco et al 2009). Surprisingly, the relationship between the age of the animals and the size of their pellets has not been specifically assessed in any of the studies conducted to date; either an average pellet size was provided for different age classes (Ball 2010) or a relationship between pellet size and the weight of the animals was shown (Southgate 2005).…”
mentioning
confidence: 98%